Hubungan Tingkat Kepatuhan Terapi Antihipertensi Dengan Kualitas Hidup Pasien Di Puskesmas Kota Padang - Primadhini, Tessa Amanda; Sari, Yelly Oktavia; Yosmar, Rahmi; Syukra, Putri Salsabila Eka Ranti; Azzahra, Rafifah; Serdiani, Serdiani (LPPM Universitas Dharma Andalas, 2025)
Hypertension is a condition diagnosed when repeated blood pressure measurements show values ≥140/90 mmHg. Long-term treatment is required to control blood pressure, making patient adherence to therapy essential for achieving therapeutic targets. Non-adherence can negatively impact patients’ quality of life, as poor health-related quality of life may limit daily functioning. The Pill Count method and the SF-36 questionnaire were used to assess medication adherence and quality of life. This study aimed to determine the relationship between antihypertensive medication adherence and the quality of life in hypertensive patients. The research was conducted at Lubuk Buaya Public Health Center from February to March 2023. It was a non-experimental analytic study using a cross-sectional method. A total of 90 participants were selected using purposive sampling. The results showed that adherence to antihypertensive medication significantly influenced only certain domains, likely due to most respondents exhibiting good adherence and high awareness, which contributed to a better quality of life. Chi-square analysis revealed a significant relationship between medication adherence and health-related quality of life, particularly in the domains of bodily pain, social functioning, and mental health.